I. T. T.: the management of opportunity - Sobel, Robert (Times Books, 1982)
"ITT is the world's largest conglomerate , a global net of more than one hundred companies engaged in an astounding variety of activities , from selling seeds and running hotels to creating the electronics - based technologies of the future . The corporation is studied at graduate business schools and dissected in the press , and has been attacked by reformers. Some consider ITT a significant expression of the American capitalist spirit , while others claim the corporation symbolizes much of what is wrong about modern business society.....(from book , courtesy of Amazon bookseller Fridamod)"